Amargo ou doce cultivo? uma análise da realidade e das lutas travadas pelas mulheres rurais no Brasil - Otesbelgue, Renata Caetano (2024)
This work proposes to analyze the struggles of rural women in Brazil, gender issues and equal rights, in the light of Law, as it incorporates much more than contractual regulations, as social justice is among its purposes, considering the laws Brazilian companies, in the effectiveness of this guarantee. From this perspective, we intend to rescue the silenced history of rural women, highlighting their contributions to the population, addressing gender discussions, the lives of these women in capitalist society and the social roles that patriarchy places on them, such as the sexual division of work to exploit their labor and make invisible their fierce subsidy to the right to food in the Brazilian domestic market, as well as their power to generate work through family and agroecological agriculture, so that the holder of capital, man white, straight and rich, accumulate more and more wealth. The present study will use the dialectical historical materialist method to support the research and intends to use the Document Analysis technique, where data on rural women will be collected from various documents such as documentaries, the Sidra/IBGE agricultural sense, among others that are aimed at to answer questions that this work proposes. It is also noteworthy that the data collected will be discussed in a qualitative way, seeking to understand the meaning and relationships expressed. In this way, the theoretical framework that will guide the theme of women and equal rights endorsed in discussions of gender, work, society and action in rural areas will have some authors highlighted, namely Heleieth Saffioti, Silvia Federici, Mary del Priore, Gerda Lerner and Zuleika Alambert, among others, who will guide the chapters of this study. In view of the above, it is hoped that this work breaks with the idea of ​​a feminism with urban roots, as rural women also need to have a voice, in a more egalitarian society under construction.